Design of a Power Amplifier Module in a Novel Silicon-Ceramic Substrate for an LTE Transmitter - Silva Cortes, Victor Arturo; Liu, Lian; Stehr, Uwe; Fischer, Michael; Frank, Astrid; Chauhan, Vikrant; Hein, Matthias; Müller, Jens; Weigel, Robert; Fischer, Georg; Hagelauer, Amelie Marietta (Asia Pacific Microwave Conference, 2017)
The present paper demonstrates the design of a power amplifier (PA) module on a silicon ceramic (SiCer) composite substrate. The SiCer platform combines the advantages of low temperature co-fired ceramic (LTCC) and silicon thin-film processing technology for micro-electro-mechanical systems (MEMS) in a quasi-monolithic composite substrate. The present approach provides a methodology for the design and manufacturing of a PA module that foresees further integration with MEMS modules such as switches, oscillators, and acoustic filters. Based on a co-simulation approach in a specification-compliant software and polyharmonic distortion modeling, the impact of the PA module in a long term evolution (LTE) transmitter is evaluated.
Keywords: Power amplifier; front end; composite substrate